Uji Pengaruh Ekstrak Daun Kirinyuh (Chromolaena odorata) Terhadap Waktu Pembekuan Darah Secara In Vitro Menggunakan Metode Lee-White - Purwaeni Purwaeni; Hesti Yulia Ningsih; Cep Wahyu (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2023)
The Kirinyuh plant comes from the Asteraceae family with the species name Chromolaena odorata. People use this plant as a traditional medicine for wound healing, an antimicrobial, anti-inflammatory, hemostatic, and coagulant. This kirinyuh plant contains flavonoids, saponins and tannins as metabolites that function to coagulate blood. This study aimed to determine the effect of adding kirinyuh (Chromolaena odorata) leaf extract on coagulant time in vitro in 16 respondents using the Lee-White method. The method used is experimental method with a total sample of 16 respondents and the sampling technique is purposive sampling. The statistical test used is the Paired Sample t-test. In examining the blood clotting time by giving kirinyuh leaf extract, the average value was 6 minutes 31 seconds, while the control obtained an average value of 7 minutes 12 seconds. The result of the Paired Sample t–test statistical test is Sig. 0.001 (p <0.05) indicates a difference between the treatment and control groups.